La Cancillería de Martín el Humano a través de los Registros Notariorum (1396-1410). - CÁRCEL ORTÍ, M. MILAGROS; ALÓS, VICENTE PONS (Scripta)
The aim of this paper is know across two records notariorum about the Archive of the Crown of Aragon those who recovered the different charges of chancellor, vice chancellor, regent of chancery, prothonotary, secretary, notary, archivist, sealer, doorman, examiner of notaries, treasurer and others during the reign of Martin I, as well as the members of his house and court as chaplain, confessor, counselor, doctor and others, besides the personnel of other royal, lordly and episcopal clerkships.